Artificial intelligence in green management and sustainability: A bibliometric survey - Niftiyev Ibrahim (E3S Web of Conferences)
The intersection of artificial intelligence (AI), green management and sustainability provides a unique opportunity to address critical environmental issues with cutting-edge technologies. The purpose of this study is to examine the developments and trends in the literature using a bibliometric analysis method. The data were collected between 1991 (January 1) and 2024 (April 1) in the Scopus database. The results show that the focus of AI and sustainability research has shifted from, for example, water management to broader environmental concerns and then to new analytical tools such as deep learning and blockchain. The most prolific and collaborative researchers come from India, China and the US and publish in already established international journals. The interdisciplinary and holistic view of AI and sustainability issues in the current study is of great interest to policy makers, key players in the market economy and other parties interested in the green transformation via AI-led technologies.